Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.